Research on an evaluation rubric for promoting user’s continuous usage intention: a case study of serious games for Chinese cultural heritage - Mao, Pingting; Cho, Dong Min (Frontiers in Psychology, 2024)
The sustainable development of serious games dedicated to Chinese cultural heritage faces challenges due to the lack of prolonged user engagement and iterative optimization based on long-term user feedback. This situation not only hinders the sustainable growth of these games but also limits the transmission of Chinese cultural heritage, a problem that demands urgent attention yet remains under-acknowledged. This study synthesizes literature to unearth user needs from three dimensions: motivational use, quality requirements of games, and continuous usage intention. It identifies fourteen influential factors, including cognitive satisfaction, immersion satisfaction, and achievement satisfaction. Drawing from the UEREG-CH evaluation rubric and the Delphi method, these factors are expanded into an evaluation system model comprising six primary indicators, fourteen secondary indicators, and thirty-eight tertiary indicators. The Analytic Hierarchy Process (AHP) is utilized for expert scoring to assign weights to each indicator. This is combined with the Fuzzy Comprehensive Evaluation method to arrive at a final user score of Z=3.4228, indicating that the evaluation rubric is close to 'good' and has received positive user feedback. Ultimately, this generates an evaluation rubric tailored to the specific context of serious games for cultural heritage. By integrating qualitative and quantitative methods, this paper confirms the scientific and rational nature of the evaluation rubric. The study aims to establish a user-approved rubric that encourages continuous usage intention, thereby providing effective guidance for game developers and assisting users in selecting appropriate games, while also addressing the theoretical gap in the field of evaluation for serious games related to cultural heritage.